Analisis Break Even Point Pada Pembuatan Cookies Dengan Pencampuran Tepung Terigu Dengan Tepung Kacang Merah - Jhoni Heni Helvandari; Ariyetti Ariyetti; Anwar Kasim (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
This study aims to analyze the amount of revenue and production of the company in a state of reaching the Break Even Point (BEP). The product that will be calculated is a product of processed cookies by mixing wheat flour with red bean flour. This research is descriptive using quantitative methods, where data collection is carried out according to the problems studied, so that the truth can be trusted. This study also uses a literature study to obtain the necessary theory and data. Based on the results of research on cookie products by mixing wheat flour with red bean flour, the BEP value in units of 4,084 cookies units and BEP in rupiah is Rp 3,012.49, so it can be concluded that this product is feasible to produce.